2021
DOI: 10.3389/frobt.2021.672934
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Phase-Change Material–Elastomer Composite and Integration in Kirigami-Inspired Voxel-Based Actuators

Abstract: Phase-change material–elastomer composite (PCMEC) actuators are composed of a soft elastomer matrix embedding a phase-change fluid, typically ethanol, in microbubbles. When increasing the temperature, the phase change in each bubble induces a macroscopic expansion of the matrix. This class of actuators is promising for soft robotic applications because of their high energy density and actuation strain, and their low cost and easy manufacturing. However, several limitations must be addressed, such as the high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…This low conductivity resulted in the heating of the soft actuator to be heavily concentrated at the contact surface of the Peltier, which causes localized expansion at the Peltier junction interface. Previous studies utilizing resistive heating [29,42] experience this problem on a smaller level, as the soft body is built around the axis of an inner coil, and the heating/expansion occurs radially. This finding led to much lower aspect ratios with relation to the Peltier surface for the application design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This low conductivity resulted in the heating of the soft actuator to be heavily concentrated at the contact surface of the Peltier, which causes localized expansion at the Peltier junction interface. Previous studies utilizing resistive heating [29,42] experience this problem on a smaller level, as the soft body is built around the axis of an inner coil, and the heating/expansion occurs radially. This finding led to much lower aspect ratios with relation to the Peltier surface for the application design.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of fluorocarbons has become limited due to their adverse impact on the ozone layer. In order to address this issue, Novec-7000, an engineering fluid with a vaporization temperature of 34 • C, has emerged as a promising alternative [41,42]. Novec-7000 has been found to be effective in managing thermal systems while being environmentally friendly.…”
Section: Working Principlementioning
confidence: 99%
“…[ 10,12 ] In our previous work, we showed that shear could also be obtained at the centimeter scale using an isotropically expansive transducer. [ 13 ] Advanced modular robots have been engineered using similar voxel‐based approaches, with either predefined bending or twisting modules [ 14 ] or reprogramable voxels which can bend, contract, and stiffen. [ 15 ] Both solutions rely on pneumatic actuation and are implemented at the centimeter scale.…”
Section: Introductionmentioning
confidence: 99%
“…[10,12] In our previous work, we showed that shear could also be obtained at the centimeter scale using an isotropically expansive transducer. [13] Advanced modular robots have been engineered using similar voxel-based approaches, with either predefined bending or twisting modules [14] or reprogramable DOI: 10.1002/aisy.202200394…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, composite-based actuators in which the bending movement is performed are also proposed and described in [ 16 , 17 ]. So far, designers of these solutions are looking for applications in the field of flexible robots, called soft robots.…”
Section: Introductionmentioning
confidence: 99%